2020
DOI: 10.15420/cfr.2020.10
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Myocardial Injury in Coronavirus Disease 2019

Abstract: Coronavirus disease 2019 (COVID-19) predominantly presents with symptoms of fever, fatigue, cough and respiratory failure. However, it appears to have a unique interplay with cardiovascular disease (CVD); patients with pre-existing CVD are at highest risk for mortality from COVID-19, along with the elderly. COVID-19 contributes to cardiovascular complications including arrhythmias, myocardial dysfunction and myocardial inflammation. Although the exact mechanism of myocardial inflammation in patients with COVID… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 59 publications
2
24
0
1
Order By: Relevance
“…The persistence of visual LGE at 3-month follow-up re ecting necrosis (persistent in ammation) or scar ( brosis) might be caused by COVID-19 and needs to be elucidated further 21 . Yet, visual LGE indicated that up to 30% COVID-19 patients have irreversible myocardial injury 22,23 , which is consistent with the ndings of the previous study and can con rm one of the main mechanisms of COVID-19 induced direct myocardial injury-myocarditis [24][25][26] . In addition, the presence of LGE has been proven to be an independent predictor of all-cause mortality and cardiac mortality in myocarditis 27,28 .…”
Section: Discussionsupporting
confidence: 91%
“…The persistence of visual LGE at 3-month follow-up re ecting necrosis (persistent in ammation) or scar ( brosis) might be caused by COVID-19 and needs to be elucidated further 21 . Yet, visual LGE indicated that up to 30% COVID-19 patients have irreversible myocardial injury 22,23 , which is consistent with the ndings of the previous study and can con rm one of the main mechanisms of COVID-19 induced direct myocardial injury-myocarditis [24][25][26] . In addition, the presence of LGE has been proven to be an independent predictor of all-cause mortality and cardiac mortality in myocarditis 27,28 .…”
Section: Discussionsupporting
confidence: 91%
“…7 In one of the first manuscripts on COVID-19 and cardiovascular effects, specifically myocardial injury, Rali et al elegantly elaborated on the different manifestations of COVID-19, explaining the cytokine storm and the myocardial picture, as well as the thrombogenicity of the virus. 16 As time allows bigger registries to be set up, we realised that impaired ventricular function as well as significant tricuspid regurgitation in patients with COVID-19 was associated with poor prognosis. 17 Lala et al.…”
Section: Covid-19mentioning
confidence: 99%
“…In one of the first manuscripts on COVID-19 and cardiovascular effects, specifically myocardial injury, Rali et al elegantly elaborated on the different manifestations of COVID-19, explaining the cytokine storm and the myocardial picture, as well as the thrombogenicity of the virus. [ 16 ]…”
Section: Heart Failure Manifestation In Covid-19mentioning
confidence: 99%
“…Myocardial abnormalities can be present, even after COVID-19 infection recovery, as previously shown (26, 27, and 28). Mechanisms involved in the onset of myocardial injury in the context of COVID-19 infection, are multiple and include hypoxemia, cytokines storm, microvascular thrombi, coronary plaque instability, systemic and vessels inflammation, myocarditis, sepsis related cardiomyopathy, stress-related cardiomyopathy and arrhythmia (29,30,31,32).…”
Section: Heart and Obesitymentioning
confidence: 99%